Persepsi Ekowisatawan Domestik Terhadap Prostitusi Di Bali - Giovanni, Gilland; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA; Vol 5 No 1 (2017): VOL 5, NO 1 (2017): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2018)
The purpose of this research was to determine the domestic ecotourist perception against prostitution in Bali. Thus, the result of this research can be used as a reference to see how far the practice of prostitution is needed in a tourist destination, especially in Bali, of course from the point of view of domestic ecotourist as one of the target tourism markets. Data collection procedures using documentation studies and questionnaire to 30 domestic ecotourist in Eka Karya Bali Botanic Garden. Data were analyzed using a likert scale, presented in tables and graphics, and describe by descriptive qualitative. The results of this research revealed that, if prostitution in Bali is categorized as a positive action is not agreed. Then, if prostitution in Bali is categorized as a negative action, was agreed.   Keywords : Domestic Ecotourist, Perception, Prostitution